2001
DOI: 10.1089/108076801753162744
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Mitomycin-C on Cultured Ciliary Process Cells and Trabecular Meshwork Cells

Abstract: Mitomycin-C has recently become an adjunct medication for inhibition of fibroblast proliferation in glaucoma filtering procedures. Prolonged postoperative ocular hypotony has been a frequent complication of trabeculectomy with mitomycin-C. In order to characterize the hypotony mechanism, we compared the toxic effects of mitomycin-C on cultured rabbit ciliary process cells and trabecular meshwork cells. The results indicate that mitomycin-C has a more marked effect on ciliary process cells on 3H-thymidine uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A previous report has identified DNA fragmentation in ciliary body tissue cultures with 0.1 mg/ml MMC applied for 3 min [33] . Suramin is expected to affect only heparin-binding cells, as it is a heparin analogue, unlike antimitotic MMC, which impacts all cells with mitotic capacity.…”
Section: Discussionmentioning
confidence: 94%
“…A previous report has identified DNA fragmentation in ciliary body tissue cultures with 0.1 mg/ml MMC applied for 3 min [33] . Suramin is expected to affect only heparin-binding cells, as it is a heparin analogue, unlike antimitotic MMC, which impacts all cells with mitotic capacity.…”
Section: Discussionmentioning
confidence: 94%
“…Cell viability was measured with MTT dye following previously published procedures [16]. The MTT assay is based on the production of purple formazan from a methyltetrazolium salt by the mitochondrial enzymes of viable cells.…”
Section: Assay Of Cell Viability With Mttmentioning
confidence: 99%
“…In one study, the toxic dose of intracameral MMC was reported to be 0.8 mg/mL 16 . In cases of accidental access of MMC to the anterior chamber, MMC may result in damage to endothelial cell, keratocyte, ciliary process and trabecular meshwork tissues 17–19 . This suggests that DW may be sufficient to prevent PCO clinically in human eye without inadvertent toxicity of MMC.…”
Section: Discussionmentioning
confidence: 99%
“…16 In cases of accidental access of MMC to the anterior chamber, MMC may result in damage to endothelial cell, keratocyte, ciliary process and trabecular meshwork tissues. [17][18][19] This suggests that DW may be sufficient to prevent PCO clinically in human eye without inadvertent toxicity of MMC. We chose silicone IOL implantation, prone to develop PCO, and rabbit eyes that have more proliferative activity Table 2.…”
mentioning
confidence: 95%